Enterprise Architectures Enable of Business Strategy and IS/IT Alignment in Manufacturing using TOGAF ADM Framework: - - Riwanto, Rengga Eko; Andry, Johanes Fernandes (International Journal of Information Technology and Business, 2019)
Manufacturing is an industry that using machinery in the production process. In this research the manufacturing is engaged in the production of the best quality pumps that used in oil palm plantations. Although this manufacture produces high quality products, but in the business process still there are several weaknesses, such as some of processes manually, systems still not integrated each other, overlapping position, etc. In this research, The Open Group Architecture Framework (TOGAF) was chosen with the Architecture Development Method (ADM) which has eight phases with focus on the business architecture phase. The expected results of this research are to be proposed TOGAF model by aligning business strategy and IS/IT, also integrating all systems and stakeholders that support business activities to achieve business goals so it will more be optimal, effective and efficient in the operational.